Ligand-controlled chemoselectivity in gold-catalyzed cascade cyclization of 1, 4-diene-tethered 2-alkynylbenzaldehydes. Issue 23 (12th October 2022) - Chen, Jichao; Hu, Rui; Bao, Qing; Shang, Dandan; Yu, Lei; Chan, Philip Wai Hong; Rao, Weidong
Abstract : A synthetic method that relies on the gold(i )-catalyzed cascade annulation of skipped 1, 4-diene-tethered 2-alkynylbenzaldehydes for the chemo- and stereoselective assembly polycyclic bridged-pyrrolidines and -azepines is described. Abstract : A method to chemo- and stereoselectively assemble polycyclic bridged pyrrolidines and azepines which relies on the gold(i )-catalyzed cascade annulation of skipped 1, 4-diene-tethered 2-alkynylbenzaldehydes is described. The divergence in product selectivity was accomplished by controlling the reaction pathway of the surmised Au-bound benzopyrylium species, generated from 6- endo-dig oxycyclization of the substrate, and by changing the steric nature of the ligand of the metal complex. With BrettPhosAuNTf2 (BrettPhos = dicyclohexyl(2′, 4′, 6′-triisopropyl-3, 6-dimethoxy-[1, 1′-biphenyl]-2-yl)phosphine) as the catalyst, the ensuing [3 + 2] cycloaddition/cyclopropanation cascade of the metal-bound cyclic oxonium intermediate was found to occur to afford the cyclopropane-fused bridged-pyrrolidine product. The presence of SIMesAuNTf2 (SIMes = 1, 3-bis(2, 4, 6-trimethylphenyl)-4, 5-dihydroimidazol-2-ylidene) as the catalyst, on the other hand, was observed to result in an Au-bound benzopyrylium intermediate undergoing a sequential [3 + 2] cycloaddition followed by selective C(sp 3 )–H bond insertion in the ensuing gold carbenoid species to give the cyclopropane-bridged-azepine ring system. The synthetic utility of the divergent catalytic protocol was demonstrated by the late-stage modification of a series of structurally complex natural products and drug molecules under mild reaction conditions.